A hTfR1 Receptor-Specific VHH Antibody Neutralizes Pseudoviruses Expressing Glycoproteins from Junín and Machupo Viruses - Qinglin Kang; Gege Li; Yan Wu; Shaoyan Wang; Zhengshan Chen; Xiaodong Zai; Xiaoyan Pan; Rong Wang; Jiansheng Lu; Peng Du; Zhixin Yang; Xiangyang Chi; et al. (Viruses)
The Junín virus (JUNV) is one of the New World arenaviruses that cause severe hemorrhagic fever. Human transferrin receptor 1 (hTfR1) has been identified as the main receptor for JUNV for virus entry into host cells. To date, no treatment has been approved for JUNV. Herein, we investigated 12 anti-hTfR1 VHH (variable domain of the heavy chain of heavy-chain antibody) antibodies and confirmed their interaction with hTfR1. Most of them could bind to the hTfR1 apical domain, which is the glycoprotein 1 (GP1) binding domain of JUNV. Among them, 18N18 exhibited neutralizing activity against both the human immunodeficiency virus (HIV)-vectored lentiviral Junín pseudoviruses and the recombinant vesicular stomatitis virus (VSV)-vectored Junín pseudoviruses. We also verified that 18N18 blocked the interaction between hTfR1 and JUNV GP1. In addition, 18N18 could neutralize another New World arenavirus, the Machupo virus. Using AlphaFold 3-based simulation of 18N18–hTfR1 docking, we determined that 18N18’s binding epitope was located at the JUNV GP1 binding epitope. 18N18 represents a candidate for JUNV treatment and provides a potential approach that could be applied to New World arenaviruses.